Archaeological heritage in the Shabè region and challenges of enhancement: the example of the “Etoo” fortified site - AGBAKA, Opêoluwa Blandine; DOGNON, Dorothée Elavagnon; LABIYI, Nestor (Edelweiss Applied Science and Technology, 2024)
The conservation and enhancement of archaeological heritage in African countries, particularly in Benin, present significant challenges for researchers. The general lack of awareness among Beninese populations regarding this heritage, coupled with its minimal integration into development and cultural policies, has led to increased degradation and, in some cases, the irreversible destruction of millennia-old relics. These artifacts bear witness to civilizations once thought extinct but remain vibrant within contemporary societies. The ETOO fortified site in the Shabè region exemplifies an archaeological site whose patrimonial value warrants preservation and promotion. This study addresses the following questions: What are the stakes involved in enhancing archaeological heritage in Benin? What heritage enhancement plan is suitable for the ETOO site in the Shabè region? How can enhancement strategies be explored through cinema and audiovisual media? The methodology combines empirical research, archaeological survey reports, and a specialized literature review, as well as a study of cinematographic and audiovisual productions on similar heritage sites in Africa and elsewhere. The objective is to present the potential of this archaeological site for heritage enhancement, identify associated threats, and reflect on the importance of archaeological heritage in territorial development plans. The article begins with a brief overview of archaeological realities in Africa, followed by an examination of the status of archaeological heritage within Beninese legislation. The third section introduces the ETOO fortified site. The final sections discuss the site's patrimonialization and analyze its potential for enhancement.